1995
DOI: 10.1159/000109772
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Multiple Sclerosis in the Provinces of Reggio Emilia and Modena, Italy

Abstract: We present the results of an epidemiological survey on MS conducted in the provinces of Reggio Emilia and Modena (4,980 km2) from 1970 to 1990. The population increased from 943,182 residents in 1970 to 1,024,223 in 1990, with an average population during the period of the survey of 993,056. The mean annual incidence was 1.59 cases/100,000 inhabitants (c.i. 95% 1.42–1.78). The prevalence as of December 31, 1990, was 39.44/100,000 inhabitants. Our study is a further demonstration that Italy is a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…An increase in the incidence rate in recent years w'as de tected also for other diseases. Such an in crease had been previously ascribed to im proved diagnostic ability and care, but ALS alone increased to such a remarkable extent (141.9%), unlike, for instance, multiple scle rosis, which had increased just in the period 1970-80 compared to the rate relevant to the period 1980-90 (72%), and did not change in the period 1980-90 [40], We think the disease frequency is likely to have truly increased in recent years, as some other au thors have suggested [41]. Our study, too, confirmed the distribution according to sex and age already reported.…”
Section: Discussionmentioning
confidence: 81%
“…An increase in the incidence rate in recent years w'as de tected also for other diseases. Such an in crease had been previously ascribed to im proved diagnostic ability and care, but ALS alone increased to such a remarkable extent (141.9%), unlike, for instance, multiple scle rosis, which had increased just in the period 1970-80 compared to the rate relevant to the period 1980-90 (72%), and did not change in the period 1980-90 [40], We think the disease frequency is likely to have truly increased in recent years, as some other au thors have suggested [41]. Our study, too, confirmed the distribution according to sex and age already reported.…”
Section: Discussionmentioning
confidence: 81%
“…Zivadinov/Iona/Monti-Bragadin/Bosco/ Jurjevic/Taus/Cazzato/Zorzon [10] 37° S 1981 71 Australia, Newcastle [9] 32° S 1981 73 Australia, Perth [9] 31° S 1981 73 Australia, New South Wales [11] 30-33° S 1981 69 Australia, South Australia [11] 27-30° S 1981 69 Brazil, City of Sao Paolo [12] 23-24° S 1981 69 Australia, Queensland [13] 10-19° S 1981 73 India, Bombay [14] 19° N 1988 70 Japan, 10 cities [15] 26-44° N 1972-1978 76 Kuwait (in Kuwaitis) [16] 28-30° N 1988 69 Kuwait (in Palestinians) [16] 28-30° N 1988 69 Libya, Benghazi [17] 32° N 1984 75 Israel, native-born Israelis whose father was born in Europe or in America [18] 34° N 1981 74 Israel, native-born Israelis whose father was born in Africa or Asia [18] 34° N 1981 74 Israel, native-born Israelis whose father was born in Israel [18] 34° N 1981 74 Israel, immigrants to Israel born in Africa or Asia [18] 34° N 1981 74 Spain, Velez-Malaga [19] 36° N 1991 69 Italy, Sicily, Monreale [20] 38° N 1991 69 Spain, Alcoy, Valencia [21] 39° N 1988 73 Greece, Northern Greece [22] 39-41° N 1984 75 Spain, Teruel [23] 39-41° N 1996 69 Italy, Sardinia, Alghero [24] 40° N 1980 70 Italy, Sardinia, Sassari [25] 41° N 1985 70 Italy, Northwestern Sardinia [26] 41° N 1991 69 Spain, Catalonia, Osona [27] 41° N 1991 69 Spain, Asturias, Gijon health district [28] 43° N 1994 69 Canada, Ontario, London County [29] 43° N 1984 70 Italy, Ferrara [30] 44° N 1993 69 Italy, Reggio Emila and Modena [31] 44° N 1990 72 Italy, Modena [32] 44° N 1990 72 USA, Minnesota, Olmsted County [33] 44° N 1 9 7 8 7 0 USA, Minnesota, Rochester [33] 44° N 1 9 7 8 7 0 USA, Minnesota, Mower County [33] 44° N 1 9 7 8 7 0 USA, Minnesota, Olmsted County …”
Section: Resultsmentioning
confidence: 99%
“…An average of recently reported MS incidence rates worldwide would approximate 3.7 per 100,000 population [6] , with a reported low of 1.7 in Reggio Emilia and Modena, Italy [14], and a high of 8.7 in Uusimaa, Finland [15] . In fact, compared to this range, the First Nations rate in Alberta at 7.6 per 100,000 population in 2002 would place it among the world's highest rates.…”
Section: Magnitude Of First Nations People Incidence Ratesmentioning
confidence: 99%